GAMBARAN LEVERAGE DAN RETURN SAHAM PERUSAHAAN SUBSEKTOR SEMEN YANG TERDAFTAR DI BEI PERIODE 2012-2016 - Mughni, Gilman; Surachim, Ahim; Tarmedi, Eded (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to obtain an overview of leverage and stock return.Design / methodology / approach - The design of this study is time series design. This research uses descriptive approach with explanatory survey method. Sample in this research are income statement of cement subsector companies which listed on IDX 2012-2016 period. The analysis technique used is descriptive technique by using leverage and stock return calculation formulas.Findings - Based on the results of the study using descriptive analysis, the results indices that leverage of cement subsector companies which listed on IDX 2012-2016 period are decrease and stock return of cement subsector companies which listed on IDX 2012-2016 period are fluctuative.Originality / value - This research provides a basic for understanding issues of leverage and stock return. The difference of this research with the previous research is located on the object this research object are cement subsector companies which listed on IDX 2012-2016 period and using theory or reference different from previous researchers.